2012
DOI: 10.1063/1.4768718
|View full text |Cite
|
Sign up to set email alerts
|

A study of temperature-related non-linearity at the metal-silicon interface

Abstract: . (2012) A study of temperature-related non-linearity at the metal-silicon interface. Journal of Applied Physics, Vol.112 . Article no. 114513 Permanent WRAP url: http://wrap.warwick.ac.uk/52407 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes the work of researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Given the small potential size of a Schottky rectenna, the impact of such interface inhomogeneity will be the source of significant device-device variation, and an unpredictability of cut-off frequencies. Typical Schottky diodes can have good diode characteristics in terms of the FOMs mentioned in Equations 18, 19 and 20, as demonstrated by the simple example of a Cr/Si Schottky diode made in-house for [155]. The characteristics of this diode are close to ideal (i.e.…”
Section: A Schottky Barrier Diodesmentioning
confidence: 86%
See 1 more Smart Citation
“…Given the small potential size of a Schottky rectenna, the impact of such interface inhomogeneity will be the source of significant device-device variation, and an unpredictability of cut-off frequencies. Typical Schottky diodes can have good diode characteristics in terms of the FOMs mentioned in Equations 18, 19 and 20, as demonstrated by the simple example of a Cr/Si Schottky diode made in-house for [155]. The characteristics of this diode are close to ideal (i.e.…”
Section: A Schottky Barrier Diodesmentioning
confidence: 86%
“…Instead, a more realistic scenario should be considered where multiple current paths exist flowing over barriers of different barrier height, so modifying this equation that has been the standard for a century or more. The papers by Tung 151,160 and others [155][156][157][158][159] pro-vide a much more rigorous understanding of the Schottky diode and its operation under this inhomogeneous regime. Given the small potential size of a Schottky rectenna, the impact of such interface inhomogeneity will be the source of significant device-device variation, and an unpredictability of cut-off frequencies.…”
Section: A Schottky Barrier Diodesmentioning
confidence: 99%
“…At low temperatures, for inhomogeneous Gr/Si interfaces, transport is dominated by the low Schottky barrier patches while with increasing temperature, more electrons have sufficient energy to surmount the higher barriers and the extracted effective barrier increases. Although reports of such temperature dependence of φ b0 and η exist in other metal/semiconductor (M/S) interfaces [15][16][17] , no clear explanation other than the consideration of an inhomogeneous distribution of barrier heights has been proposed 18 . For Gr/Si interfaces, inhomogeneity in barrier heights arise due to local modification of graphene work function by the nonuniform interface charge distribution caused by unavoidable potential fluctuations due to ripples 9 and/or formation of graphene grain boundaries 10 etc.…”
Section: Resultsmentioning
confidence: 99%
“…From the I-V plot in Figure 5a, we can see that the current at the forward region is linear at voltage ≤0.5 V and starts to deviate from linearity due to series resistance, R s . The double bumps that were normally due to other transport mechanisms such as generation-recombination, thermionic field emission, and field emission, were not observed in this case [26,54,55]. This is also an indication that thermionic emission starts to dominate at the temperature range tested.…”
Section: Extraction Of Schottky Parametersmentioning
confidence: 65%
“…Although the homogeneity of TiSi 2 is better than GNW, the lack of micro heat sink characteristic in TiSi 2 causes a much higher temperature effect on the leakage current. Another study done by Gammon [26] on metal with different homogeneity also showed that inhomogeneous metal would require a large carrier concentration to activate all the patches with low barrier height, while the homogenous interface requiring less carrier concentration to activate the patches. Therefore, the leakage current for the homogeneous interface could be higher than the inhomogeneous surface.…”
Section: Electrical Characterizationmentioning
confidence: 95%